Harmonizing Clinical Excellence: Assessing Workflow Synergy and Interprofessional Communication across Dentistry, Physiotherapy, Nursing, Pharmacy, Radiology, and Laboratory Units - Alessa, Abdullah Ahmed Mohammed; Alsaif, Abdulaziz Saad; Mahzari, Mohammed Yahya Yahya; Alenezi, Maha Shamsi Malouh; Alshammri, Abdullah Mady Ayed; Alotaibi, Mohammed Abdullah Mohammed; AlFaheed, Mohammad Fahad; Alshahrani, Amerah Bedah; Alharthi, Abdullah Ahmed Hamed; Saleh, Wafa Mohammed Bin; et al. (Journal of Posthumanism, 2024)
Background: The modern healthcare landscape is paradoxically defined by advanced specialization and systemic fragmentation. While deep expertise in individual disciplines—dentistry, physiotherapy, nursing, pharmacy, radiology, and laboratory sciences—drives clinical innovation, the resulting operational silos often obstruct the seamless flow of patient information. This systematic review investigates the "silo mentality" as a primary driver of preventable medical errors, diagnostic delays, and therapeutic inefficiencies. Objectives: Adopting a PICO framework, this review compares Intervention 1 (Integrated, Interprofessional Workflows) against Intervention 2 (Traditional, Siloed Workflows) within a global context. The primary objective is to evaluate the impact of harmonized communication protocols (e.g., ISBAR, Multidisciplinary Rounds) and cross-disciplinary integration (e.g., pharmacists in radiology, physiotherapists in ICU rounds) on patient safety, clinical efficiency, and staff satisfaction. Methods: A comprehensive synthesis of global literature published was conducted, encompassing quantitative trials, qualitative assessments, and systematic reviews. Data sources span high-resource settings in Europe and North America, as well as resource-limited environments in Africa and Southeast Asia. The review applies robust quality assessment tools to evaluate the efficacy of interventions across the six target disciplines. Results: The evidence overwhelmingly supports the superiority of integrated workflows. In diagnostic settings, the integration of clinical pharmacists into radiology units reduced contrast-induced nephropathy and allergic events by over 60%. In critical care, early mobilization protocols coordinated between physiotherapy and nursing, governed by strict laboratory value guidelines, achieved a 90% adherence rate to daily goals with zero serious adverse events. Furthermore, the implementation of Multidisciplinary Rounds (MDR) in cardiovascular units was associated with a reduction in in-hospital mortality from 2.8% to 1.6%. Conversely, siloed workflows were characterized by significant communication failures, with up to 83% of primary care physicians reporting delays in receiving critical test results. Conclusions: Harmonizing clinical excellence requires a paradigm shift from proximity to true synergy. The integration of distinct professional identities into a cohesive care team is not merely an administrative enhancement but a clinical imperative. The data suggests that future healthcare models must prioritize structural communication tools, interprofessional education (IPE), and digital interoperability to bridge the chasm between disciplines.